PENGEMBANGAN PERANGKAT ASESMEN KETERAMPILAN MENULIS TEKS EKSPLANASI DAN CERITA PENDEK SERTA IMPLEMETASI DALAM KURIKULUM 2013 - Sauhenda, Angla Florensy; Riwu, Lay; Tembang, Yonarlianto (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2018)
Assessment is a process to obtain and collect student learning outcomes during learning. Based on the facts in the field it was found that the teacher was unable to compile assessment tools for writing explanatory text skills and short story texts. The purpose of this study was to develop assessment tools for explanatory text writing skills and short story texts consisting of teacher guides and student assignments. The research and development model used in this study is the R2D2 development model. The results showed that the assessment skills of explanatory text writing skills and short story texts developed were appropriate to be implemented in the 2013 curriculum. The teacher's guide to explanatory texts reached 91% and the teacher's guide to short story texts reached 86%. While the student assignment for the explanatory text reached 87% and the student assignment for the short story text reached 82%. Based on the results of the validity and reliability test, it shows that all the items of work that have been developed are valid and reliable.